PENERAPAN MEDIA PEMBELAJARAN FLIPBOOK UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN IPAS MATERI EKOSISTEM DI KELAS V UPT SD - Siregar, Hotma Tiolina; Tarigan, Juniko Esra; Rahmadini, Viralya (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2025)
This research aims to increase student learning motivation by implementing flipbook-based learning media, a tool for measuring student learning motivation in implementing interactive flipbook learning media using questionnaires. Questionnaire used the questionnaire that the researcher will use is a closed questionnaire consisting of 4 indicators from which 19 questions are made. The data obtained from the questionnaire is then processed and analyzed using a Likert scale. After analysis, it was obtained that the student learning motivation questionnaire data regarding the application of interactive flipbook learning media obtained an average of 88.46% in the ST category (very high). For each indicator, students gave a high response to interactive flipbook learning media. Based on the average results, it can be concluded that students are motivated to learn using interactive Flipbook learning media in science subjects, especially ecosystem material.